1981
DOI: 10.1111/j.1943-278x.1981.tb00995.x
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Death Experiences and Attempted Suicide

Abstract: Attempted suicide is correlated with an increase subsequent risk of committed suicide. However, preliminary data and psychodynamic hypotheses suggest that serious suicide attempts followed by transcendental near-death experiences (NDEs) may decrease rather than increase subsequent overt suicide risk, despite the NDEs' apparent "romanticization" of death. Studies of NDEs and of their influence on suicidal ideation are proposed which may yield greater understanding of self-destructive urges and new strategies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…People who have had NDEs do not take their own lives, and my data support recent studies that indicate that even repeated suicide attempters, once they have had an NDE, do not generally attempt to take their lives again (Greyson, 1981(Greyson, , 1986. My final question concerned the most significant change to come about as a result of the NDE.…”
Section: Discussionsupporting
confidence: 72%
“…People who have had NDEs do not take their own lives, and my data support recent studies that indicate that even repeated suicide attempters, once they have had an NDE, do not generally attempt to take their lives again (Greyson, 1981(Greyson, , 1986. My final question concerned the most significant change to come about as a result of the NDE.…”
Section: Discussionsupporting
confidence: 72%
“…Later studies involved interviewing all members of a group of individuals likely to have been close to death. Although some of the earlier cohort studies focused on accident victims [10,23,24,119] or survivors of attempted suicide [30,[120][121][122][123][124], more recent ones have focused on survivors of cardiac arrest [5][6][7][8]14,61,125]. Limiting the sample to cardiac arrest survivors maximizes the possibility that the study participants were indeed close to death, but as noted above, NDEs associated with cardiac arrest may not be typical of NDEs associated with other circumstances.…”
Section: Methodological Issues In Scientific Research Into Ndesmentioning
confidence: 99%
“…On the contrary, all NDE researchers report that most Western people who have an NDE experience a sense of well-being, peace, joy, and cosmic unity (Greyson 1985;Moody 1975;Owens, Cook, and Stevenson, 1990;Ring 1984;Sabom 1982). Bruce Greyson (1981) further reported that people who attempt suicide (often construed as the ultimate cultural no-no) and who then have an NDE report just as positive experiences as people whose NDE came as a result of acci dents, operations, or fatal illness. In other words, Western NDEs are not simple confirmations of cultural expectation.…”
Section: The Relation Of Ndes To Cultural Expectation Of the Nature Omentioning
confidence: 99%